Penerapan Model Pembelajaran Project Based Learning (PjBL) dengan Aplikasi Capcut untuk Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran Videografi di SMK PGRI Ciawigebang - Meidi, Meidi; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to examine the application of the Project Based Learning (PjBL) learning model combined with the CapCut application in increasing student learning motivation in Videography learning at SMK PGRI Ciawigebang. The research method used is a quantitative approach. The research sample is grading XI students majoring in Visual Communication Design. With a total of 32 students. The results showed that the application of the PjBL model with the CapCut application significantly increased students' learning motivation. The use of CapCut not only makes it easier for students to edit videos, but it also provides them with practical skills that are relevant to the industry. The PjBL learning model with the CapCut application has a positive influence on student learning motivation. The results of the questionnaire showed that student motivation in using CapCut learning media was in the very high category, with a percentage of 87%. This shows that students feel more motivated and enthusiastic in the learning process when using relevant and interesting applications. There was a significant difference in students' learning motivation before and after the implementation of the PjBL model with the CapCut application. The average learning motivation of students in the pretest was 50.00, while after the application of this learning method, it increased to 69.06